دور السياحة في تعزيز قيم المواطنة لدى الشباب: دراسة ميدانية لعينة من الشباب في ولاية الخرطوم - أحمد، محمد يس يس محمد (مركز بحوث ودراسات دول حوض البحر الأحمر وجامعة شندي, 2020)
تتناول هذه الدراسة دور السياحة في تعزيز قيم المواطنة لدى الشباب بالتطبيق على الشباب في ولاية الخرطوم، وأن تفعيل قيم المواطنة لدى الشباب له أهمية قصوى في تحقيق الاستقرار والتطور. وهنا تبرز الحاجة لتعزيز هذه القيم الوطنية لدى الشباب. تهدف هذه الدراسة إلى معرفة تأثر السياحة في تعزيز قيم المواطنة لدى الشباب، بالإضافة إلى التعرف على الجوانب الحياتية ذات العلاقة بتعزيز قيم المواطنة لدى الشباب. اعتمدت هذه الدراسة على المنهج الوصفي التحليلي بالإضافة إلى المنهج التاريخي، أما مصادر جمع المعلومات فتم الاعتماد على المصادر الأولية والثانوية من مراجع وكتب وتقارير بالإضافة إلى الاستبيان. قد توصلت الدراسة إلى عدة نتائج من أهمها، تعد قيم المواطنة من القضايا ذات الأبعاد السياسية والأمنية التي يجب الاهتمام بها، وأيضاً غياب مفهوم وفلسفة السياحة بين الشباب في السودان مما انعكس سلباً على حركة السياحة، وعدم وجود دراسات علمية تخص الشباب مما انعكس سلبياً على عدم الاستفادة من مقدرات الشباب. كما خرجت الدراسة بعدة توصيات أهمها ضرورة الاهتمام بالشباب بصورة عامه، والاهتمام بالمواقع السياحية في السودان، ومواجهة الهجمات الفكرية والسياسية المتطرف التي تواجه الشباب وتحصينهم ضد هذه الهجمات بتعزيز قيم المواطنة والانتماء للوطن، مما ينعكس إيجابياً على الشباب.
This study addresses the role of tourism in promoting the values of youth citizenship application on youth in Khartoum, to activate civic values among young people is of paramount importance in achieving. Stability and evolution, and here there is a need to strengthen these national values among young people. This study aims to find out the impact of tourism in promoting civic values among young people, in addition to identifying relevant aspects of life promoting civic values among youth. This study adopted a descriptive analytical plus the historical method, information-gathering sources, Reliance on primary and secondary sources of references and books and reports in addition to the questionnaire might study found several of the most important results, the civic values of issues of political and security dimensions that need attention, and also the absence of the concept and philosophy of tourism among youth in Sudan, Reflected negatively on tourist traffic, and the lack of scientific studies concerning youth which reflected negatively on the failure to take advantage of the potential of youth as the study emerged several recommendations, notably the need to pay attention to young people in General and tourist sites in Sudan, and intellectual and political attacks Extremist facing youth and immunized against these attacks by promoting the values of citizenship and belonging to the country, which has a positive impact on youth.
Keywords: السياحة -- البرامج السياحية -- الشباب -- ولاية الخرطوم -- المواطنة